Re-Examining the Finance-Growth Nexus: Empirical Evidence from Indonesia - Abd. Majid, M. Shabri (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This paper empirically examines the short- and long-run relationships between financial development and economic growth during the post-1997 financial crisis in Indonesia by employing a battery of times-series techniques, such as Autoregressive Dis-tributed Lag (ARDL) model, vector error correction model (VECM), variance decompositions (VDCs), and impulse-response functions (IRFs). Based on the ARDL (2, 0, 1, 2) model, the study finds that there exists a long-run equilibrium between economic growth and financial depth, share of investment, and inflation. In the long run, inflation is found to be the only variable which significantly (negatively) affects economic growth, implying a crucial role of maintaining a low rate of inflation in promoting the economic growth in the country. As for the dynamic causalities among the variables, the study finds the bidirectional causation between economic growth and investment, while the unidirectional causation is only found running from financial depth to investment. The finding of independence between economic growth and financial development supports the view of âthe independent hypothesisâ of Lucas (1988). Finally, based on VDCs and IRFs, the study documents that the variations in the economic growth respond more to shocks in the price stability (inflation), followed by investment and financial development. Our findings indicate that if policy makers want to promote growth, attention should be focused on long-run policies, i.e., maintaining the low rate of inflation.